Wide-angle light scattering (WALS) for soot aggregate characterization - Oltmann, Hergen; Reimann, Joerg; Will, Stefan (Combustion and Flame, 2010)
A novel set-up for the experimental determination of aggregate morphology in combustion processes based on elastic light scattering has been designed and realized. A key feature of this wide-angle light scattering (WALS) approach is an ellipsoidal mirror which is used to collect scattered light over a wide angular range of about 10-170 degrees. The set-up employs a cw solid-state laser as light source and an intensified CCD-camera as detector. By means of the mirror the scattered light is imaged onto the detector allowing for a simultaneous acquisition of a full scattering diagram with a high angular resolution of about 0.6 degrees. To demonstrate the performance of the approach, measurements for various sooting flames produced by premixed combustion in a flat flame burner were carried out, where the burner was operated with different equivalence ratios and fuels. It is shown that radii of gyration of soot particles may efficiently be obtained from an analysis of the scattering diagrams. (C) 2009 The Combustion Institute. Published by Elsevier Inc. All rights reserved.
Keywords: Light scattering; Soot aggregate morphology; Ellipsoidal mirror; Wide angular range